Structural, optical, and electrical characterization of the poly[9, 9‐dioctylfluorenyl‐2, 7‐diyl]‐co‐1, 4‐benzo‐(2, 1, 3)‐thiadiazole thin film fabricated by electrostatic spray technique. Issue 3 (30th May 2013) - Mustafa, Maria; Kim, Hyung Chan; Doh, Yang‐Hui; Choi, Kyung Hyun
<x xml:space="preserve">Abstract</x> The article presents the efficient fabrication of the Poly[9, 9‐dioctylfluorenyl‐2, 7‐diyl]‐co‐1, 4‐benzo‐(2, 1, 3)‐thiadiazole (F8BT) thin film using the electrostatic spray technique. Electrostatic atomization of the in‐house developed F8BT polymer ink was achieved at considerable low voltage. The structural and optical characterizations of the fabricated F8BT thin film were thoroughly investigated. Furthermore, the organic diode structure with electrostatic spray deposited F8BT thin film was fabricated and its performance was analyzed by performing current voltage measurement. The current–voltage characteristic curve of the organic diode showed nonlinear diode like behavior, thereby confirming the proper interference established between organic diode adjacent layers. The space charged limited current mechanism has been found to be dominant in the fabricated organic device with carrier mobility value of 5.65 e−4 cm2V−1s−1. POLYM. ENG. SCI., 54:675–681, 2014. © 2013 Society of Plastics Engineers